Declining Sexual Activity and Desire in Men—Findings From Representative German Surveys, 2005 and 2016. Issue 5 (1st May 2018) - Beutel, Manfred E.; Burghardt, Juliane; Tibubos, Ana N.; Klein, Eva M.; Schmutzer, Gabriele; Brähler, Elmar
Abstract: Background: Surveys have indicated an increase of sexual activity in aging men; recently, however, a decrease of sexual activity has been reported in young men. Aim: To assess (i) sexual activity and desire and their determinants across the age range in a population-based male sample and (ii) their changes over 11 years. Methods: A representative survey of men (N = 1, 095) 18 to 93 years old from 2016 was compared with a survey from 2005 (N = 1, 106 men) with the same age range. Samples were drawn from the German population at random using standardized sampling procedures. Questions were filled out by participants in the presence of a trained interviewer. Sexual activity was compared using logistic regression with the factors survey (2005 vs 2016), living with a partner (yes vs no), and age. Frequency of sexual desire was compared using analysis of covariance with the factors survey (2005 vs 2016), living with a partner (yes vs no), and the covariate age. Outcomes: Sexual activity was assessed as having been intimate with someone in the past year; frequency of sexual desire was evaluated within the past 4 weeks. Results: The great majority of men cohabiting with a partner in 2016 was sexually active and indicated sexual desire until 70 years of age; half did so at an older age. Across the age range, men living without a partner reported considerably less sexual activity and desire. Compared with 2005, fewer men reported living with a partner. The overall proportion of men reporting sexual activity deceased from 81% to 73% in 2016 and absent sexual desire increased from 8% to 13%. Clinical Translation: The findings highlight the relevance of living with a partner for sexual activity and desire. We advocate using a measure of sexual activity that encompasses many variants of intimate behavior. Strengths and Limitations: Large and methodologically comparable population-based samples were compared. However, interpretations are limited by the absence of longitudinal data. We did not assess the effect of having a partner living elsewhere. Conclusion: Sexual activity and desire decreased, especially in the young and middle-age groups. The decrease of men living with a partner contributed to this decreased sexual activity and desire. There was a generation effect, with younger and middle-age men living without a partner becoming less sexually active and experiencing less desire compared with the previous survey. The findings unveil changes in sexual activity and desire in a short time span.